2012
DOI: 10.1517/17425247.2012.696606
|View full text |Cite
|
Sign up to set email alerts
|

Current development in nanoformulations of docetaxel

Abstract: Although nanoformulations such as liposome, micelle, nanoparticle, nanoemulsion greatly improve the solubility, activity and distribution of DTX in vivo, significant hurdles remain concerning aspects of nanoformulations such as quality control, physicochemical stability, storage conditions, large-scale production and controlled manufacture technology, in vivo metabolism, excretion, acute and chronic toxicity, etc. In-depth studies in these areas are essential to making DTX nanoformulations applicable in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 70 publications
0
52
0
Order By: Relevance
“…In recent years paclitaxel has been delivered in an albumin bound formulation (Abraxane ® ) used in breast cancer treatment [31]. Over the years, many investigators have been trying to develop paclitaxel nanoformulations that retain the anti-tumor properties of paclitaxel but reduce the non-specific toxicity related to the vehicles in which paclitaxel is delivered [32][33][34][35]. Many studies have shown that nanotechnology has a great potential not only to improve the characteristics of drugs that are hydrophobic and require the use of toxic solvents for delivery, but also increases the specificity of drugs by increasing the delivery of the drug to the targeted sites [20,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years paclitaxel has been delivered in an albumin bound formulation (Abraxane ® ) used in breast cancer treatment [31]. Over the years, many investigators have been trying to develop paclitaxel nanoformulations that retain the anti-tumor properties of paclitaxel but reduce the non-specific toxicity related to the vehicles in which paclitaxel is delivered [32][33][34][35]. Many studies have shown that nanotechnology has a great potential not only to improve the characteristics of drugs that are hydrophobic and require the use of toxic solvents for delivery, but also increases the specificity of drugs by increasing the delivery of the drug to the targeted sites [20,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…12 These side effects are attributable to either DTX as a cytotoxic agent or the presence of P80. 2,13 Stability data showed that the premix solutions are stable for 8 hours at room temperature or under refrigeration, and diluted infusion solution are stable for 4 hours at room temperature. 14 The main reason for the short storage time is the potential risk of precipitation of the infusion solution during storage, which are affected by various factors such as insufficient mixing of the premix solutions, temperature, and excessive agitation.…”
Section: Current Issues: Safety Efficacy and Deliverymentioning
confidence: 99%
“…2 Gajbhiye and Jain developed P80-anchored poly(propyleneimine) (PPI) dendritic nanoconjugate for delivery of DTX targeted to brain tumor. 44 The DTX-P80-PPI dendrimers showed better antitumor efficacy and higher penetration in brain tumor than both DTX-PPI and free DTX.…”
Section: Dendrimersmentioning
confidence: 99%
See 2 more Smart Citations